2015
DOI: 10.1016/j.nlm.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent upregulation of multiple plasticity factors in the hippocampus during early REM sleep

Abstract: Sleep is beneficial to learning, but the underlying mechanisms remain controversial. The synaptic homeostasis hypothesis (SHY) proposes that the cognitive function of sleep is related to a generalized rescaling of synaptic weights to intermediate levels, due to a passive downregulation of plasticity mechanisms. A competing hypothesis proposes that the active upscaling and downscaling of synaptic weights during sleep embosses memories in circuits respectively activated or deactivated during prior waking experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 74 publications
8
34
0
1
Order By: Relevance
“…Neuronal firing rates during REM sleep showed robust temporal dependence across brain regions: while changes in cortical firing rates during object exploration predicted hippocampal firing rates during REM sleep in the first hour post-experience, changes in hippocampal firing rates during object exploration predicted cortical firing rates during REM sleep in the third hour post-experience. Along with other lines of evidence [157,158,165,173], this corroborates the hypothesis that REM sleep is important for the stabilization of memory traces within cortico-cortical connections, specially in supragranular and infragranular layers [65].…”
Section: A Role For Rem Sleep In Memory Corticalizationsupporting
confidence: 86%
See 3 more Smart Citations
“…Neuronal firing rates during REM sleep showed robust temporal dependence across brain regions: while changes in cortical firing rates during object exploration predicted hippocampal firing rates during REM sleep in the first hour post-experience, changes in hippocampal firing rates during object exploration predicted cortical firing rates during REM sleep in the third hour post-experience. Along with other lines of evidence [157,158,165,173], this corroborates the hypothesis that REM sleep is important for the stabilization of memory traces within cortico-cortical connections, specially in supragranular and infragranular layers [65].…”
Section: A Role For Rem Sleep In Memory Corticalizationsupporting
confidence: 86%
“…More recently, these results were extended to the IEG Fos and two major phosphatases related to LTD [174,175], Ppp2ca and Ppp2r2d (Fig. 2c) [165]. This result offers direct support to the notion that sleep-dependent memory processing is a complex, multifaceted process comprising both synaptic potentiation and synaptic depression, as proposed by the Synaptic Embossing Theory.…”
Section: A Role For Rem Sleep In Memory Corticalizationsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, the underlying plastic synaptic processes that enable representational transformations at the neuronal level are established during SWS [24,25]. However, other studies have suggested that some aspects of memory abstraction and the underlying synaptic plasticity involve REM sleep (e.g., [115][116][117]). The issue is complicated by observations indicating that the presumed abstraction process develops more or less slowly, depending on the stimulus material and preexisting knowledge, and thus may manifests itself at retrieval only with some delay, and not immediately after the experimental sleep period [118,119].…”
Section: Box 2 Contributions Of Rem Sleep To Memory Consolidation -Amentioning
confidence: 99%